Second pulmonary resection for a second primary lung cancer: analysis of morbidity and survival. (24th December 2020) - Abid, Walid; Seguin-Givelet, Agathe; Brian, Emmanuel; Grigoroiu, Madalina; Girard, Philippe; Girard, Nicolas; Gossot, Dominique
Abstract:  : OBJECTIVES: Evaluating morbidity and survival of patients operated on for a second primary non-small-cell lung cancer (NSCLC). METHODS: Retrospective collection of data from patients operated on for a second NSCLC between 2009 and 2018. RESULTS: Fifty-two patients met the inclusion criteria. At the time of second pulmonary resection, the median time between the 2 surgeries was 25 months (5–44.5 months). Patients' median age was 65 years (61–68 years). Median tumour size was 16 mm (10–22 mm). Thoracoscopy was used in 75% of cases. The resection was a pneumonectomy ( n  = 1), bilobectomy ( n  = 1), lobectomy ( n  = 15), segmentectomy ( n  = 32) or wedge resection ( n  = 3). The length of stay was 7 days (5–9 days). Mortality was null and morbidity was 36.5%, mainly from grade I–II complications according to the Clavien–Dindo classification. The median follow-up was 28 months (13–50 months). The median overall survival was 67 months (95% confidence interval 60.8–73.1 months). Survival at 5 years and specific survival were 71.1% and 67.7%, respectively. CONCLUSIONS: A second surgical resection of either synchronous or metachronous NSCLC has a morbidity that is not superior to the morbidity of the first operation. The new tumour is usually diagnosed at an early stage. An anatomical sublobar resection is most likely the best compromise. It might also be considered for the first operation when there is a suspicious synchronous lesion that may require surgery at a later stage.